Kill painting of hypoxic tumors with multiple ion beams. (8th February 2019) - Sokol, O; Krämer, M; Hild, S; Durante, M; Scifoni, E
Abstract: We report on a novel method for simultaneous biological optimization of treatment plans for hypoxic tumors using multiple ion species. Our previously introduced kill painting approach, where the overall cell killing is optimized on biologically heterogeneous targets, was expanded with the capability of handling different ion beams simultaneously. The current version (MIBO) of the research treatment planning system TRiP98 has now been augmented to handle 3D (voxel-by-voxel) target oxygenation data. We present a case of idealized geometries where this method can identify optimal combinations leading to an improved peak-to-entrance effective dose ratio. This is achieved by the redistribution of particle fluences, when the heavier ions are preferentially forwarded to hypoxic target areas, while the lighter ions deliver the remaining dose to its normoxic regions. Finally, we present an in silico skull base chordoma patient case study with a combination of 4 He and 16 O beams, demonstrating specific indications for its potential clinical application. In this particular case, the mean dose, received by the brainstem, was reduced by 3%–5% and by 10%–12% as compared to the pure 4 He and 16 O plans, respectively. The new method allows a full biological optimization of different ion beams, exploiting the capabilities of actively scanned ion beams of modern particle therapy centers. The possible experimental verification of the present approach at ion beam facilities disposing of fast ion switch is presented and discussed.